Chloroplast envelope K+/H+ antiporters are involved in cytosol pH regulation - Rodríguez-Rosales, María Pilar; Rubio-Valverde, Lourdes; Pedersen, Jesper; Aranda-Sicilia, María Nieves; Fernández, J.A.; Venema, Kees (Wiley, 2024)
Variations in light intensity induce cytosol pH changes in photosynthetic tissues, providing a possible signal to adjust a variety of biochemical, physiological and developmental processes to the energy status of the cells. It was shown that these pH changes are partially due to the transport of protons in or out of the thylakoid lumen. However, the ion transporters in the chloroplast that transmit these pH changes to the cytosol are not known. KEA1 and KEA2 are K+/H+ antiporters in the chloroplast inner envelope that adjust stromal pH in light-to-dark transitions. We previously determined that stromal pH is higher in kea1kea2 mutant cells. In this study, we now show that KEA1 and KEA2 are required to attenuate cytosol pH variations upon sudden light intensity changes in leaf mesophyll cells, showing they are important components of the light-modulated pH signalling module. The kea1kea2 mutant mesophyll cells also have a considerably less negative membrane potential. Membrane potential is dependent on the activity of the plasma membrane proton ATPase and is regulated by secondary ion transporters, mainly potassium channels in the plasma membrane. We did not find significant differences in the activity of the plasma membrane proton pump but found a strongly increased membrane permeability to protons, especially potassium, of the double mutant plasma membranes. Our results indicate that chloroplast envelope K+/H+ antiporters not only affect chloroplast pH but also have a strong impact on cellular ion homeostasis and energization of the plasma membrane.
Keywords: Cloroplastos; Células vegetales; Arabidopsis thaliana; K+/H+ antiportters; Chloroplast; Cytosolic pH